Perceptions and Expectations of Primary School Third Grade Pupils on General Studies* (Sachunterricht) Course: Case of Germany - Z. Nurdan BAYSAL; Zeynep DİLBER ÖZER (Anı Publishing, 2021)
The present study attempts to reveal the perceptions of 3rd-grade pupils toward the general studies (Sachunterricht) course. In this regard, the subjects liked or disliked by the pupils, materials and pupils' perceptions on the general studies course were determined. The study employed phenomenology which is one of qualitative research methods. This study was conducted with 41 pupils enrolled in two different primary schools in Stuttgart, the capital city of the German state of Baden- Württemberg. The data were collected through an open-ended questionnaire called "General Studies Perception Scale", the drawings by the pupils and their explanations on the drawings. The research data were analyzed via descriptive and content analysis methods. In the study, it was found that the pupils liked all the subjects in this course. In addition, the most frequently- used materials by the pupils during the course were pencil, glue, paper, and scissors. It was ascertained that most of the pupils wanted the subjects in the general studies course to be integrated with art. Besides, pupils are conducting a lot of experiments and would like to continue doing experiments. Based on the study outcomes, it was suggested that certain precautions must be taken for the subjects included in the content of social sciences to be liked by the pupils in general studies course and exam and worksheet applications must be limited.